Multiple Intelligence-Based Strategies for Civic Learning in Primary Schools - Assingkily, Muhammad Shaleh; Wulandari, Yeni; Kharis Sulaiman Hasri (Yayasan Zia Salsabila, 2025)
Pancasila character education in Indonesian elementary schools faces significant challenges due to learning approaches that do not accommodate the diversity of multiple intelligences of students, thus potentially ignoring the unique potential of each child in internalizing Pancasila values. This study aims to develop a multiple intelligence-based civic education learning strategy to improve Pancasila character in elementary school students, with an emphasis on optimizing all dimensions of intelligence possessed by students. A systematic literature review method was used by analyzing articles indexed by Google Scholar, Science and Technology Index (SINTA), and SCOPUS on the themes of Pancasila, civic education, character education, and multiple intelligences. The results of the study indicate that the integration of multiple intelligence theory in Pancasila character learning can optimally improve the quality of internalization of national values, by adjusting pedagogical strategies to the diversity of student intelligence types such as linguistic, logical-mathematical, kinesthetic, musical, interpersonal, intrapersonal, visual-spatial, and naturalist. The practical implications of this research provide guidance for educators to create an inclusive and equitable learning environment, so that each student can develop a humanist attitude and Pancasilaist character according to their respective intelligence potential, without anyone being left behind in the process of forming national character.